THE IMPORTANCE OF PRELIMINARY AND PERIODIC MEDICAL EXAMINATIONS IN THE DETECTION OF METABOLIC SYNDROME IN EMPLOYEES OF ORGANIZATIONS AND THE GENERAL POPULATION (World Bulletin of Public Health, 2025)
Metabolic syndrome is one of the key medical and social problems of modern society, due to the growing prevalence of obesity, type 2 diabetes, and cardiovascular diseases. This problem is particularly relevant in the working-age population, where chronic non-communicable diseases directly affect labor productivity and quality of life. The article examines the role of preliminary and periodic medical examinations as an effective tool for early detection of metabolic syndrome among employees and the general population. It analyzes modern diagnostic criteria, organizational aspects of medical examinations, and the possibilities for prevention and correction of identified disorders. The study concluded that systematic medical examinations are highly important for reducing the risk of complications and promoting a preventive healthcare model.
Keywords: metabolic syndrome; metabolic syndromemedical examinations; prevention; screening